Increasing women's visibility in the bean value chain in Cameroon - Ngoh, Siri Bella; Nchanji, Eileen Bogweh (2022)
Women’s role in agri-food system are varied but are often not visible as they are not considered farmers but helpers. This has resulted to women having limited access to productive agricultural resources. Women should be at the centre of activities in the agrifood systems hence involving women at all levels of the value chain. women are not a homogenous group, so intersectionality categories should guide the process. We are cognizant of the fact that bean businesses are mostly family businesses with different household members playing different roles, therefore our interventions target men, women and youths within the households.